Electrochemical sensor for sulfide determinationin food additives - Jian Chu; Wentan Guo (Functional Materials, 2018)
This study is devoted to using of electrochemical sensor based on multiwalled carbon nanotube-nanogold composite membrane for detection of sulfite which is one of harmfull food additives. The experimental results demonstrated that the application of electrochemical sensor could improve electron transport rate and increase electrode surface and effective contact area of solution. Sulfite in dried bean milk cream in tight rolls could be effectively detected using voltammetric method. This work provides a reference for the application of electrochemical sensor in detection of food additives.